Empowerment of Productive Waqf Funds for Stunting Prevention from the Perspective of Sharia Economics - A'inil Fadli; Regina Marcella; Fadhil Ahmad Alkarimi (Saqifah: Jurnal Hukum Ekonomi Syariah, 2024)
Stunting is a serious health problem in Indonesia, characterized by stunted physical growth in children due to prolonged malnutrition. One way to overcome this problem is to strengthen productive waqf funds for stunting prevention. For this reason, we first need to understand what is the concept of productive waqf; then what is the strategy in empowering waqf funds; and how is the implementation of waqf programs in stunting prevention; and how Sharia economics views productive waqf empowerment for stunting prevention. In order to answer this question, the researcher conducted a legal research method that uses several approaches to draw conclusions based on the historical, comparative and conceptual aspects of this research. In the end, it can be concluded that Waqf, as an Islamic economic instrument, has great potential to support stunting prevention programs by improving the welfare of the community through Waqf asset management, which aims to generate income that can be used for social and economic purposes. In the context of stunting prevention, waqf funds can be used for programs that improve families' access to nutritious food, education, health, and increased family income.